Modelling the Price of Unleaded Petrol in Australia’s Capital Cities - Abbas Valadkhani (Australasian Accounting, Business and Finance Journal, 2010)
This paper examines the long-run and short-run determinants of unleaded petrol price in Australia’s capital cities using monthly data to find out whether prices respond asymmetrically to external shocks. Based on the cointegration test results and the estimated asymmetric short-run dynamic models, it is found that: (1) in the long-run petrol prices are mainly determined by Tapis crude oil and Singapore petrol prices; (2) there is some evidence of asymmetric price adjustments in the short-run since petrol price increases have been mostly passed on to the consumer faster than price decreases in four capital cities. More specifically, this paper provides convincing evidence in support of asymmetric price adjustments and the “rockets-and-feathers hypothesis” in Adelaide, Brisbane, Melbourne and Sydney. One can thus argue that there are a significant degree of market inefficiency and/or collusion, requiring a closer government price monitoring and scrutiny.
Keywords: Unleaded petrol prices; Australia; Asymmetric ECM models